2008
DOI: 10.1007/s11999-008-0456-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Hip Resurfacing Arthroplasty in Patients with Developmental Hip Dysplasia

Abstract: Patients with osteoarthritis secondary to developmental dysplasia of the hip (DDH) typically are young and active, which might affect functional ratings or failure rates after resurfacing arthroplasty. We therefore evaluated 24 patients (32 hips; mean age, 44.2 years) after hip resurfacing performed for osteoarthritis secondary to DDH. We used the Harris hip score (HHS), the University of California, Los Angeles (UCLA) activity scale, and a sports and activity questionnaire. A radiographic analysis also was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…Additionally, 68% of the patients had a HOOS score greater than 80 points for all five categories and 85% of patients had postoperative regular involvement in moderate physical activities for the return to previous physical activities, a new demand in this type of population [18,38,43]. No patient reported thigh pain when asked, whereas numerous studies of conventional cementless stems showed some rates of thigh pain as much as 27% [8,25,35,44].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 68% of the patients had a HOOS score greater than 80 points for all five categories and 85% of patients had postoperative regular involvement in moderate physical activities for the return to previous physical activities, a new demand in this type of population [18,38,43]. No patient reported thigh pain when asked, whereas numerous studies of conventional cementless stems showed some rates of thigh pain as much as 27% [8,25,35,44].…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that the outcomes for HRA are worse for dysplasia than for OA patients [24,25]. In Amstutz's early study of dysplasia [18], there were more problems on the femoral side with a femoral neck fracture rate of 8.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Conservation of bone stock, not only on the femoral side, is an increasingly important issue in THA, considering the demographics of patients are changing toward an increasing proportion of younger and more active individuals [17][18][19]. These patients in their 40s and 50s are likely to undergo revision THA later during life, which would be aggravated by compromised bone stock owing to excessive bone removal during primary THA [3,19].…”
Section: Discussionmentioning
confidence: 99%
“…The life expectancy of these patients, mainly in their 40s and 50s, may exceed 30 years. Many patients seek hip arthroplasty relatively early and do not accept activity restrictions after surgery [17,18]. Therefore many of these patients likely will require additional hip surgery or revision arthroplasty later in their lives.…”
Section: Introductionmentioning
confidence: 99%